2012
DOI: 10.1063/1.4769261
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser guiding of a high-voltage discharge and the restoration of dielectric strength in air and nitrogen

Abstract: The use of a low energy, high peak intensity (>100 TW/cm2) femtosecond laser pulse is investigated for guiding and control of a sub-microsecond high voltage discharge. Study of the laser induced plasma channel and measurements of the field required for breakdown in air and nitrogen at atmospheric pressure are presented. Direct imaging of the dynamics of the discharge breakdown shows effective laser guiding. The effectiveness of laser guiding is shown to be critically dependent on the laser focusing geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 17 publications
2
20
1
1
Order By: Relevance
“…The phenomenon we have described should not be confused with the laser guiding of (streamer) discharges described by [27,28] and others, where focused high power lasers create a thin channel with an electron and ion density of 10 16 -10 17 cm −3 in atmospheric air, while the ionization inside a streamer channel amounts to 10 15 cm −3 at most. Such laser channels modify the background electric field at least one order of magnitude more rapidly than a streamer, and effectively act as conductors.…”
Section: Comparison With Other Laser Guiding Experimentssupporting
confidence: 60%
See 1 more Smart Citation
“…The phenomenon we have described should not be confused with the laser guiding of (streamer) discharges described by [27,28] and others, where focused high power lasers create a thin channel with an electron and ion density of 10 16 -10 17 cm −3 in atmospheric air, while the ionization inside a streamer channel amounts to 10 15 cm −3 at most. Such laser channels modify the background electric field at least one order of magnitude more rapidly than a streamer, and effectively act as conductors.…”
Section: Comparison With Other Laser Guiding Experimentssupporting
confidence: 60%
“…Furthermore, in the other studies [28,29] the laser is usually aligned parallel to the field lines. Here we have shown that very weakly ionized regions that are almost perpendicular to the local field lines can still guide the streamers.…”
Section: Comparison With Other Laser Guiding Experimentsmentioning
confidence: 99%
“…The amplitude of the microwave electric field in the channel for the general case of scatterers with dielectric permittivity ε and conductivity σ when channels are thin compared to skin depth ( mm for microwave frequency ~10.58 GHz use in this work) can be written as:where k - depolarization factor governed by the channel geometry, E 0 - incident microwave electric field at the channel location3233. The depolarization factor k for the channels with large aspect ratio m = l/d ≫ 1 is small: 343536.…”
Section: Methodsmentioning
confidence: 99%
“…The discharge position is detected right in mixing layer of some pairs of gases involved. Finally, it was demonstrated that the discharge channel position can be effectively tailored by a little energy beam of a femtosecond laser [39]. Recently, the mixing intensification in high-speed flow due to filamentary discharge generation was experimentally proven by means of analysis of flow disturbances and measurements of local fuel concentration by method of probe breakdown fluorescence [40].…”
Section: Mixing Enhancement Experimentsmentioning
confidence: 99%